1981
DOI: 10.1111/j.1471-4159.1981.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Affinity Uptake of Spermine by Slices of Rat Cerebral Cortex

Abstract: The accumulation of the polyamine spermine into 0.1-mm prisms of rat cerebral cortex has been investigated at both 37 percent C and at 4 percent C. Kinetic analysis of the temperature-sensitive portion of uptake indicates two high-affinity saturable components together with an unsaturable component at high concentrations. The "very high'-affinity saturable system (K(m)= 3.8 nM) was temperature- and sodium-dependent, and significantly reduced by metabolic inhibitors, finding that are consistent with an active t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 28 publications
1
21
1
1
Order By: Relevance
“…Since the uptake of 5.7 x 1O-9M tPH]-spermine is sodium-dependent. temperaturedependent and strongly susceptible to inhibition by metabolic inhibitors (Harman & Shaw, 1980b), properties which are consistent with neuronal transport, the release of spermine at this concentration in response to raised potassium concentrations may possibly reflect the depolarization of neuronal elements. Evidence is increasing that the potassiumevoked release of GABA from preparations which are rich in glia is independent of the presence of calcium ions (Sellstrom & Hamberger, 1977;Neal & Bowery, 1979) though Minchin & Iversen (1974) have reported calcium-dependent release from glia in rat dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Since the uptake of 5.7 x 1O-9M tPH]-spermine is sodium-dependent. temperaturedependent and strongly susceptible to inhibition by metabolic inhibitors (Harman & Shaw, 1980b), properties which are consistent with neuronal transport, the release of spermine at this concentration in response to raised potassium concentrations may possibly reflect the depolarization of neuronal elements. Evidence is increasing that the potassiumevoked release of GABA from preparations which are rich in glia is independent of the presence of calcium ions (Sellstrom & Hamberger, 1977;Neal & Bowery, 1979) though Minchin & Iversen (1974) have reported calcium-dependent release from glia in rat dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 96%
“…The potassium-induced release of spermine is only found to be calcium-dependent at an initial spermine uptake concentration of 5.7 x 10-9 M [:'H]-spermine. At this concentration, approximately 85% of the uptake occurs via a 'very high' affinity system (Km = 3.7 x 10-9 M) (Harman & Shaw, 1980b). On increasing the spermine uptake concentration, release is no longer calcium-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work with ODC inhibitors has suggested that significant nolvamine accumulation can occur in the absence of ODC r 2 activity (23,25), and some estimates of polyamine reutilization rates indicate that as little as 30% of brain putrescine originates directly from the decarboxylation of ornithine (28). Because brain tissue, in particular, contains active uptake mechanisms for putrescine and the polyamines (29,30), acquisition of these compounds may be regulated separately from that of ODC during development. The question of whether similar mecha- Fig.…”
Section: Discussionmentioning
confidence: 99%